Peluang Dan Ancaman Perdagangan Produk Kakao Dan Kebijakan Untuk Mengatasinya : Studi Kasus Indonesia Dengan Malaysia - Tia Octaviany; Sandri Antora; Yanatul Asnah; Ai Nursiti (CV. ITTC INDONESIA, 2024)
ABSTRACT Globalization has brought changes in international trade because the world market situation has entered a period of globalization. If a country is able to export and import a commodity, then that country will specialize in manufacturing that commodity, which will result in an increase in the country's productivity by lowering the cost of producing each unit. In particular, this requires so-called intra-industry trade, that is, the exchange of goods originating from the same industrial sector. The majority of Indonesian cocoa exports are still made from cocoa beans, even though Indonesia is the third largest cocoa exporter in the world. As a result, Indonesia loses a large amount of value that might be obtained from cocoa-derived goods. The main objective of this research is to determine the extent of intra-industry trade in cocoa commodities from Indonesia and Malaysia.